Perubahan iklim dan dinamika penduduk dalam konteks kebijakan nasional di Indonesia - Nurlambang, Triarko; Rizqihandari, Nurrokhmah (Jurnal Kependudukan Indonesia, 2012)
A variety of research results and data indicate that the symptoms of climate change have become more real. This can also be seen in Indonesia, although the extreme symptoms have not yet been made apparent due to its location, which is around the equator and is dominated by oceans. In general, the displacement areas in Indonesia are concentrated in the coastal areas. These areas have a high level of risk since they also serve as concentration activity points for most of the Indonesian population. Unfortunately, the adaptation capacity and mitigation activity in Indonesia are still relatively limited, even though they have been supported by funds from international donors. In the meantime, policies and regulations in connection with the anticipation of climate change symptoms and population control are still in an early stage; specifically, the awareness stage. It is not possible to be able to say that both policies and regulations have effectively progressed.